On the sizes of least common multiples of stars versus cycles - Wang, Ping (Utilitas Mathematica, 1998)
If G and H are nonempty graphs, then H is said to be G-decomposable if E(H) can be partitioned into sets E1,E2, . . . , En such that the subgraph induced by each Ei, i = 1, 2, . . . , n, is isomorphic to G. If H has no isolated vertices and is a graph of minimum size which is both G1-dcomposable and G2-decomposable, where G1 and G2 are nonempty graphs, then H is called a least common multiple of G1 and G2. The size of a least common multiple of G1 and G2 is denoted by lcm(G1,G2). Some special cases of a conjecture about lcm(C2n+1, Kl,1) by G. Chartrand et al. are proved. We also give a counterexample to show when it is false and give some comments and an improved conjecture.